2002
DOI: 10.1207/s15548430jlr3401_1
|View full text |Cite
|
Sign up to set email alerts
|

The Performance and Construction of Subjectivities of Early Adolescent Girls in Book Club Discussion Groups

Abstract: This study examines the performance and construction of subjectivities of four early adolescent, sixth-grade girls as they read and discussed a novel about two adolescent Mexican children seeking a new life in America. Using data gathered through ethnographic methods such as participant-observation, interviews, dialogue journals, and book club discussions, the author describes the participants as they performed their subjectivities in various contexts, focusing specifically on their performances while reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
1
10
0
3
Order By: Relevance
“…The role that the multicultural literature played in the RTW club in my research is congruent with how the students in studies such as Broughton's (2002) and Vyas's (2004) responded positively to literature that depicted characters like themselves. Nevertheless, it is important to note studies that utilized multicultural literature but that did not elicit personal responses from students.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The role that the multicultural literature played in the RTW club in my research is congruent with how the students in studies such as Broughton's (2002) and Vyas's (2004) responded positively to literature that depicted characters like themselves. Nevertheless, it is important to note studies that utilized multicultural literature but that did not elicit personal responses from students.…”
Section: Discussionsupporting
confidence: 67%
“…(p. 20-21) Many studies in literacy research have utilized this format to explore students' identities and identity construction, such as Latina middle school girls (Broughton, 2002), Asian high school girls (Vyas, 2004), African American and white girls (Smith, 2005), and African American high school girls (Sutherland, 2005). Although literacy scholars have included minority adolescents in their research, the studies continue to display a limited range in terms of featuring minority students beyond certain already established research populations, which constitutes a significant gap in the literature (Dressman & Webster, 2001).…”
Section: Foregrounding the After School Literacy Sitementioning
confidence: 99%
See 1 more Smart Citation
“…I have considered this "norming" process in relation to community standards and masculinity in boys' responses to literature (Pace & Lowery, 2001). However, this effect is also quite visible in girls' public responses in literature discussions (Barbieri, 1995;Broughton, 2002;Brown & Gilligan, 1992;Finders, 2001). This research suggested that girls do not publicize personal perceptions that counter gender-role stereotypes (e.g., Broughton, 2002;Cherland, 1994;Enciso, 1998).…”
Section: Social Issues Inside Interpretive Communitiesmentioning
confidence: 97%
“…These norms, established through implicit or tacit transactions between teacher and students and among students, become the standards by which the student views herself as participant. In this sense, social interaction in classroom settings provides the context in which students and teachers construct, reconstruct, and give meaning to their subjectivities and their actions (Broughton, 2002;Lewis, 1997;McCarthey, 1998).…”
Section: Subjectivities and Classroom Participationmentioning
confidence: 99%